Rational design and synthesis of mesoporous silica nanostructure-based drug delivery systems - Chlebanowski, Lauren (Kansas State University, 2019)
Among the most threatening diseases in the world, cancer and multi-drug resistant bacteria infections are two of the most serious. Mesoporous silica nanoparticles or nanostructures (MSNs) provide nanovesicles for transporting anti-cancer or anti-microbial drugs. The MSNs can easily be functionalized with gatekeepers to ensure that these drugs are released when and where they are needed. It is known that membrane disruption is more difficult for bacteria to gain resistance. For this reason, a small surfactant library was designed with potential of having significant activity toward both gram-positive and gram-negative bacteria. Once the surfactants were synthesized, they were characterized using NMR, IR, and mass spectroscopy. Their activity was then tested against Micrococcus luteus and Methicillin Resistant-Staphylococcus aureus. The surfactants with best activity were then successfully incorporated into MSN structures. Benzalkonium chloride (BAC), a commercially available antiseptic, had the lowest minimum inhibitory concentration (MIC) of the surfactants tested, thus making it the best candidate for use in the proof of study for the designed delivery system. The MSN-based system for treatment of bacterial infections consisted of BAC loaded, amine functionalized MSNs anchored to a vancomycin gatekeeper via a protease cleavable peptide linker. The peptide was designed to have two cleavage positions by proteases for optimal cleaving. Vancomycin was chosen for its bulky size and activity toward bacteria. The system designed for treatment of cancer was focused on the non-specific nature of the therapeutic peptide SA-D-K₆L₉-AS. The peptide needed to be “gift-wrapped” and sent to the exact location of the tumor to minimize systemic toxicity. The proposed system for this was to use MSNs built directly around a self-assembling version of D-K₆L₉, then embedding iron oxide nanoparticles on the surface of the MSN, and finally enveloping the MSN in a lipid membrane. The drug would be released when the iron oxide particles were heated via radio-wave mediated hyperthermia. As proof of concept, MSNs built around a rhodamine-B labeled, self-assembling version of D-K₆L₉ were used and tested against GL26 (glioma), B16F10 (melanoma), and NSC (neural stem cells) cell lines, both with and without the gatekeeping system. The outcome was as anticipated, the gatekeeper kept the peptide inside and the cell viabilities remained high. The next steps of these projects will be to continue in-vitro testing before moving on to mouse model studies. The MSNs in both projects were characterized using DLS, Zeta potential, TGA, and TEM. Overall, the proposed MSN-based drug delivery systems appear to exhibit promising potential for new approaches towards treatment of both antibiotic resistance and cancer.
Keywords: Nanotechnology; Antibiotic resistance; Cancer; Mesoporous silica; Peptides